The Influence of Past Racism on Criminal Injustice: A Review of The New Jim Crow and The Condemnation of Blackness - Jefferson Exum, Jelani (American Studies, 2012)
This essay reviews The New Jim Crow: Mass Incarceration in the Age of Colorblindness by Michelle Alexander; and The Condemnation of Blackness: Race, Crime and the Making of Modern Urban America by Khalil Gibran Muhammad.